Consumer Protection Against Nopia Products That do Not Include Expiration Dates - Atun, Devi Windy (Journal of Legal and Cultural Analytics, 2025)
Consumers are people who use an item. Every consumer who buys or uses a product certainly hopes to get a good product and as desired. The development of the global economy makes consumers have many choices, because the food offered is increasingly diverse and varied. This is also caused by consumers who pay less attention to their rights and lack of awareness as consumers. Meanwhile, consumer protection is a matter of interest for humans, therefore consumer protection is the hope for this nation tobe able to realize the relationship between business actors and consumers who have a mutually beneficial and not detrimental relationship. This research aims to determine and analyze the protection of consumers for products that do not include an expiration date. This research uses normative juridical research methods which are methods carried out through library research or examining the main data, namely secondary data. Legal protection for consumers against nopia products that do not include expiration dates is regulated in Articles 4 and 29 of Law Number 8 of 1999 concerning Consumer Protection, where consumer rights must be implemented by business actors with the right to obtain information, the right to security, and the right to safety after consuming the product.